CicloGis: um Banco de Dados Geográficos para apoiar ciclistas de Belém do Pará - ALVES, Pedro Paulo Vieira (2024)
This article details the development of a cyclist database in Belém using geoprocessing technologies. The goal is to provide an efficient tool for mapping routes, identifying points of interest, and enhancing the safety and mobility of cyclists in the city. Geospatial data collection and geographic analysis techniques were employed to create an accessible and user-friendly system. The outcome is a database that facilitates navigation, promotes cycling as a sustainable mode of transportation, and supports urban planning focused on active mobility